Low Voltage Power MOSFETs Design, Performance and Applications - Korec, Jacek; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Low Voltage Power MOSFETs focuses on the design of low voltage power MOSFETs and the relation between the device structure and the performance of a power MOSFET used as a switch in power management applications. This SpringerBriefs close the gap between detailed engineering reference books and the numerous technical papers on the subject of power MOSFETs. The material presented covers low voltage applications extending from battery operated portable electronics, through point of load converters, internet infrastructure, automotive applications, to personal computers and server computers. The issues treated in this volume are explained qualitatively using schematic illustrations, making the discussion easy to follow for all prospective readers.
MOSFET Basics -- Application Requirements -- Power MOSFET Performance -- MOSFET Generations -- Sync Buck Optimization.
Keywords: Engineering; Electronics; Production of electric energy or power; Engineering; Power Electronics, Electrical Machines and Networks; Solid State Physics; Electronics and Microelectronics, Instrumentation